Perceptions, attitudes, and beliefs toward giraffes in Northern Kenya. Issue 2 (4th March 2022) - Ruppert, Kirstie A.; Sponarski, Carly C.; Masiaine, Symon; Larpei, Lexson; Lekushan, Johnson; Lenaipa, Daniel; Lenyakopiro, Jonathan; Lerapayo, Sebastian; Stacy-Dawes, Jenna; O`Connor, David; Glikman, Jenny A.
ABSTRACT: Giraffe populations are in continued decline and there is limited work on the human dimensions of giraffe conservation. This article assessed relationships among human dimensions concepts (normative belief, attitude, existence belief, perceptions) specific to the reticulated giraffe species ( Giraffa reticulata ) in northern Kenya. Data from in-person structured interviews with community conservancy members in two areas ( n = 584) indicated that these concepts differed by study area, but overall, respondents felt positively toward this species of giraffe, valued giraffes as very important, and believed that giraffe populations should increase. Perceived benefits were positively related to both attitudes toward and existence beliefs about giraffes, although results provide less evidence of positive associations between cognitions about giraffes and normative beliefs. These findings support that conservation messaging should be tailored to localized contexts, providing implications for integration of human dimensions information into giraffe conservation efforts.